2017
DOI: 10.1007/s00382-017-3943-z
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between Atlantic Niño variability and ocean dynamics

Abstract: operate in the model. Due to the small zonal extent of the equatorial Atlantic, the observed Bjerknes feedback acts quasi-instantaneously during the dynamically active periods of boreal summer and early boreal winter. Then, all elements of the observed Bjerknes feedback operate simultaneously. The model cannot reproduce this, although it hints at a better performance when using bias reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 52 publications
5
43
0
Order By: Relevance
“…While the (total) Bjerknes feedback is asymmetrical in winter, it does not project onto the observed SST variability—indicating that the Bjerknes feedback plays a minor role in establishing the Atlantic winter Niño. This agrees with Dippe et al () who have found that dynamical, Bjerknes feedback‐related contributions to Atl3 SST variability do increase in winter, but are much smaller in magnitude than in summer. Rather than being a dynamically driven phenomenon as in the Pacific, the Atlantic winter Niño appears to be much more susceptible to atmospheric noise forcing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While the (total) Bjerknes feedback is asymmetrical in winter, it does not project onto the observed SST variability—indicating that the Bjerknes feedback plays a minor role in establishing the Atlantic winter Niño. This agrees with Dippe et al () who have found that dynamical, Bjerknes feedback‐related contributions to Atl3 SST variability do increase in winter, but are much smaller in magnitude than in summer. Rather than being a dynamically driven phenomenon as in the Pacific, the Atlantic winter Niño appears to be much more susceptible to atmospheric noise forcing.…”
Section: Discussionsupporting
confidence: 92%
“…While the (total) Bjerknes feedback is asymmetrical in winter, it does not project onto the observed SST variability-indicating that the Bjerknes feedback plays a minor role in establishing the Atlantic winter Niño. This agrees with Dippe et al (2018) who have found that dynamical, Bjerknes feedback-related contributions to Atl3 SST variability do increase in winter, Figure 13. Decadal variations of ERSST-SST event strengths along the equator (x axis) for running subperiods (y axis, shown dates label the start of each analysis period) in the Pacific (left column, a-c) and the Atlantic (right column, d-f).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite the large biases of climatological SST in the region, models are able to reproduce reasonably the Atlantic Niño and the Bjerknes feedback (Deppenmeier et al, ). Ding et al () and Dippe et al () show that an improved mean state of the TA can lead to better representation of interannual variability in the Kiel climate model, suggesting that error in the climatological SST could be related with errors in the interannual variability.…”
Section: Introductionmentioning
confidence: 99%